Ação da terapia fotodinâmica antimicrobiana sobre biofilmes orais crescidos in vitro e in situ - Teixeira, Alrieta Henrique (2010)
The treatment of diseases caused by oral biofilms involves mechanical removal and use of antibiotics and antiseptics which can lead to problems of bacterial resistance. Photodynamic antimicrobial chemotherapy (PACT) represents an alternative option to conventional treatment, promoting bacterial killing by photo-sensitization of microbial components. This study assessed the antimicrobial action of photodynamic therapy on oral biofilms produced in vitro and in situ using a light emitting diode (LED) associated with the photosensitizer toluidine blue O (TBO). Biofilms of Streptococcus mutans UA159 were grown on hydroxyapatite discs immersed in bathing culture and submitted to PACT after 5 days. For the in situ study, twenty-one volunteers were previously selected to use intra-oral palatal appliances containing eight blocks of human dentin during 7 days. Sucrose solution (10%) was dripped onto the dental blocks 8 times a day. The biofilm formed on one side of the device received treatment (PACT), and the opposite side acted as control. The collected material has gone through a process of disruption to the dispersion of cells and diluted in decimal series (10-1 to 10-4). In both experiments, specific culture media for the growth of total streptococci and mutans streptococci were inoculated and incubated under optimal conditions for growth of these microorganisms. Significant reductions in excess of 99.99% (p<0.05) were observed in the viability of colonies of S. mutans UA159 when exposed to TBO and LED on in vitro study. However, the biofilms formed in situ and subjected to the same experimental conditions showed no statistically significant differences (p≥0.05) in the microbiological counting when compared with control group. Therefore, we conclude that PACT was effective in microbiological reduction of S. mutans UA159 grown in an in vitro biofilm model, but very little effective on oral streptococci biofilms produced in situ.